2014
DOI: 10.1186/s40508-014-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

High performance green barriers based on nanocellulose

Abstract: With the increasing environmental concerns such as sustainability and end-of-life disposal challenges, materials derived from renewable resources such as nanocellulose have been strongly advocated as potential replacements for packaging materials. Nanocellulose can be extracted from various plant resources through mechanical and chemical ways. Nanocellulose with its nanoscale dimensions, high crystalline nature, and the ability to form hydrogen bonds resulting in strong network makes it very hard for the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
166
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(175 citation statements)
references
References 58 publications
9
166
0
Order By: Relevance
“…Therefore, the tortuosity increases within the sheets due to the formation of this dense network, which lowers the permeability. In addition to fiber size, fiber entanglement plays an important role in the increase of tortuosity 40 . Studies have shown that nano-fibrillated cellulose (NFC) has longer fiber sizes compared to crystalline nano-cellulose (CNC) 40 .…”
Section: Effect Of Al2o3 Film Thickness On Gas Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the tortuosity increases within the sheets due to the formation of this dense network, which lowers the permeability. In addition to fiber size, fiber entanglement plays an important role in the increase of tortuosity 40 . Studies have shown that nano-fibrillated cellulose (NFC) has longer fiber sizes compared to crystalline nano-cellulose (CNC) 40 .…”
Section: Effect Of Al2o3 Film Thickness On Gas Permeabilitymentioning
confidence: 99%
“…In addition to fiber size, fiber entanglement plays an important role in the increase of tortuosity 40 . Studies have shown that nano-fibrillated cellulose (NFC) has longer fiber sizes compared to crystalline nano-cellulose (CNC) 40 . However, the gas permeability of the CNC film is higher than that of the NFC film due to the higher entanglement of fibrils within the NFC films which results in increase of the tortuosity factor 40 .…”
Section: Effect Of Al2o3 Film Thickness On Gas Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…CNC-based barrier films have potential applications in batteries, filtration devices, and packaging, and paper products (Khan et al, 2012;Zhou and Wu, 2012;Lalia et al, 2013). These CNC-based packaging materials could be used for prolonging the shelf-life of pharmaceutical, food and drink products, protecting against physical, biochemical, and microbiological degradation and deterioration (Nair et al, 2014). To be effective, CNC-based packaging materials should provide sufficient mechanical strength, barrier against air, water vapor, light, microorganisms, and external contaminants (Spence et al, 2011).…”
Section: Biochemical: "Green" Barrier Filmsmentioning
confidence: 99%
“…Due to extensive hydrogen bonding, the dense CNC networks decrease the permeability within the CNC-based films or composites, making it difficult for the gas and other external molecules to pass through. Furthermore, due to size and swelling constraints, CNCs have strong inhibitory effect on water vapor diffusion (Nair et al, 2014). The major advantage lies in the tunability of the CNCs' barrier properties, which can be obtained by changing the packing density.…”
Section: Biochemical: "Green" Barrier Filmsmentioning
confidence: 99%